PENERAPAN KONSEP KARAOKE EKSKLUSIF BERGAYA KONTEMPORER PADA DESAIN INTERIOR RUANG KARAOKE SELYN LOUNGE & RESTO PALEMBANG - Miadiputri, Arthia Zahra; Subkiman, Anwar (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2024)
Selyn Lounge & Resto Palembang applies a hybrid restaurant concept, where during the day it functions as a family dining place and at night it turns into a restaurant bar with live music and karaoke entertainment. By implementing this concept, harmony is needed so that the restaurant & bar concept with karaoke entertainment facilities can be unified and equal. Karaoke as the main entertainment facility requires a differentiator because of the widespread competition between karaoke. To answer this competition, an exclusive karaoke concept with a contemporary style has been implemented in the karaoke room. The application of the Design Thinking Method can be used to help answer design problems to produce solutions based on the conditions, desires, and needs of users by using several design elements that are processed based on the stages of the Design Thinking Method so that the resulting design solution is by the target user. Keywords: Exclusive Karaoke, Desain Thinking, Restaurant Hybrid Abstrak Selyn Lounge & Resto Palembang menerapkan konsep restaurant hybrid yang dimana pada siang hari berfungsi sebagai tempat makan keluarga dan pada malam hari berubah menjadi restaurant bar dengan hiburan live music dan juga karaoke. Dengan diterapkannya konsep tersebut, dibutuhkan keselasaan agar konsep restaurant & bar dengan fasilitas hiburan karaoke dapat menyatu dan setara. Karaoke sebagai fasilitas hiburan utama memerlukan adanya suatu pembeda karena maraknya persaingan antar karaoke. Untuk menjawab persaingan tersebut, maka diterapkan konsep karaoke eksklusif dengan gaya kontemporer pada ruang karaoke. Penerapan Metode Design Thinking dapat digunakan untuk membantu menjawab permasalahan desain untuk menghasilkan solusi berdasarkan kondisi, keinginan dan kebutuhan pengguna dengan menggunakan beberapa elemen desain yang diolah berdasarkan tahapan pada Metode Design Thinking, sehingga solusi desain yang dihasilkan sesuai dengan target pengguna. Kata Kunci: Karaoke Eksklusif, Desain Thinking, Restaurant Hybrid